Analisis Persepsi Atas Faktor-Faktor Yang Berpengaruh Terhadap Keinginan Seseorang Menjadi Whistleblower (Studi Kasus pada Mahasiswa S1 Akuntansi Perguruan Tinggi Negeri dan Swasta di Kota Padang) - Riani Sukma Wijaya (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to determine the perception of students to become a whistleblower based on the role of students. This study uses independent variables (X) such as Agent of Change (X1), Social Control (X2), and Iron Stock (X3), and the dependent variable (Y) is the student's perception to become a whistleblower (Y). Its population is undergraduate student of Accountancy Force 2014 registered in State and Private University in Padang City.This research uses purposive sampling method, that is sampling by using certain criteria. The number of samples in this study were 80 students. The data collection method used is by distributing questionnaires. Data analysis method used is classical assumption test, multiple linear regression analysis, and coefficient determination test, while to test the hypothesis used t test, and F test with the help of SPSS version 21. Instrument data collection using questionnaires with likert scale which respectively tested and tested and qualified for validity and reliability.The result of this research shows that the variable of agent of change, social control and iron stock with the value of coefficient of determination (Adjusted R Square) is 0,533 or 53,3% that influence student perception to become a whistleblower while the rest 46,7% influenced by other variables not examined in this study. Partially, the variable of agent of change have positive and significant influence to the perception of the student to become a whistleblower with the level of significance value (0,021), social control variable have positive and significant influence to the student perception to become a whistleblower with significance value level (0,007) and variable of iron stock has a positive and significant effect on the students' perception to become a whistleblower with significance level (0.001).Variable agent of change, social control and iron stock simultaneously have a positive influence on students' perception to become a whistleblower, it is seen from the value of F arithmetic of 31,048 with significance value (0.000).